Parts Behave Differently in Wholes - Schilbrack, Kevin (Journal for the study of religion, nature and culture, 2021)
Sophie Gibb, Robin Findlay Hendry, and Tom Lancaster (eds.), The Routledge Handbook of Emergence (New York: Routledge, 2019), 420pp., $245.00 (cloth), ISBN: 978-1138925083. Stuart A. Kauffman, A World beyond Physics: The Emergence and Evolution of Life (Oxford: Oxford University Press, 2019), 151pp., $24.95 (cloth), ISBN: 978-0190871338. Mariusz Tabaczek, Emergence: Towards a New Metaphysics and Philosophy of Science (Notre Dame: University of Notre Dame Press, 2019), 396pp., $75.00 (cloth), ISBN: 978-0268104979.